Assessing potential environmental influences on killer whale (Orcinus orca) distribution patterns in the Bremer Canyon, south-west Australia. Issue 3 (3rd July 2019) - Jones, Alexandra; Bruce, Eleanor; Davies, Kevin P.; Blewitt, Michelle; Sheehan, Scott
ABSTRACT: Submarine canyons play an important role in the regional distribution, abundance and dispersal of marine biota and are increasingly being recognised as geomorphic features of high conservation significance along Australia's continental margin. Certain canyons have been described as foraging 'hotspots' attributable to the high abundance of apex cetacean species aggregating in these areas. Anecdotal evidence of large seasonal aggregations of killer whales in the Bremer Canyon, south-west Australia, has attracted significant research attention in the last decade. To identify important environmental drivers influencing aggregation patterns, a predictive spatial habitat model using the Maxent model was developed based on presence-only whale sighting data. In addition, remotely sensed sea surface temperature and chlorophyll- a concentrations were assessed to investigate the spatio-temporal variation in sea surface conditions. Habitat preference was predicted in areas between canyon heads, with the most influential predictor variables being depth and distance from the continental shelf break. Analysis of remote-sensing data highlighted low localised variability in surface waters and illustrated the seasonal trends of the Leeuwin Current. This study demonstrates the influence of bathymetry and submarine geomorphology on enhanced cetacean abundance and highlights the need for recognition of this potential foraging area in marine reserve planning.